TEACHING READING THROUGH READING, ENCORE, ANNOTATE AND PONDER (REAP) TECHNIQUE TO THE SEVENTH GRADERS - Arriyani, Nurfisi; Oktaviani, Oktaviani (English Community Journal, 2019)
This research is aimed to find out whether the implementing of REAP strategy could improve students’ reading comprehension achievement. From the 24 samples as experimental group and 24 remain for the control group, the writer collected the data by giving the pre-test and post-test and analyze it by using Independent sample t-test. The result showed the value of t-obtained 3.868, at the significant level p < 0.05 for two tailed and degree of freedom (df) was 46, t-table was 1.678. Since the value of t-obtained was higher than t-table, it could be assumed there was significantly difference in the students reading comprehension achievement after the students were taught REAP as a teaching technique.